2022
DOI: 10.1186/s12957-022-02810-z
|View full text |Cite
|
Sign up to set email alerts
|

High co-expression of immune checkpoint receptors PD-1, CTLA-4, LAG-3, TIM-3, and TIGIT on tumor-infiltrating lymphocytes in early-stage breast cancer

Abstract: High expression of immune checkpoint receptors (ICRs) in the tumor microenvironment regulates the anti-tumor response. In this study, the differential expressions of ICRs on tumor-infiltrating lymphocytes (TILs) in patients with early-stage breast cancer were investigated.The study included 32 patients who underwent surgery with a diagnosis of early-stage breast cancer between September 2018 and March 2020. TIL isolation was performed using a MACS tumor separation device and tumor separation kit. PD-1, CTLA-4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Mollavelioglu et al. (2022) also found that TIGIT on tumor‐infiltrating lymphocytes (TILs) was highly co‑expressed with other immune checkpoint receptors like programmed cell death protein 1 (PD‐1), cytotoxic T lymphocyte–associated antigen 4 (CTLA‐4), LAG‑3, and TIM‑3 in early‑stage breast cancer. However, in several clinical trials, the immune checkpoint inhibitors have been used in patients with breast cancer, only a small percentage of them benefit (Cejuela et al., 2022).…”
Section: The Ways F Nucleatum Promotes Tumor Proliferation and Metast...mentioning
confidence: 99%
“…Mollavelioglu et al. (2022) also found that TIGIT on tumor‐infiltrating lymphocytes (TILs) was highly co‑expressed with other immune checkpoint receptors like programmed cell death protein 1 (PD‐1), cytotoxic T lymphocyte–associated antigen 4 (CTLA‐4), LAG‑3, and TIM‑3 in early‑stage breast cancer. However, in several clinical trials, the immune checkpoint inhibitors have been used in patients with breast cancer, only a small percentage of them benefit (Cejuela et al., 2022).…”
Section: The Ways F Nucleatum Promotes Tumor Proliferation and Metast...mentioning
confidence: 99%
“…In healthy human donors, CTLA-4 expression on NK cell populations is low, and associated with decreased production of activating cytokines and an increase in IL-10 production ( 355 ). CTLA-4 expression was found on mediastinal lymph node-derived NK cells of NSCLC patients ( 375 ) and on tumor infiltrating NK cells in early-stage lung cancer ( 376 ).…”
Section: Receptor Driven Signaling In Natural Killer Cellsmentioning
confidence: 99%
“…In addition, the increased co-expression of TIM-3 along with PD-1, CTLA-4, LAG-3, and TIGIT on TILs in early breast cancers (BCs) has indicated these immune checkpoints might synergistically inhibit the response to the tumor. 42 Hence, from a therapeutic point of view, the combined inhibition of these immune checkpoints may synergistically enhance the T-cell response to various tumor antigens. In this context, the in vitro study of combined PD-L1 and TIM-3 blockade indicates enhanced expansion of fit human CD8 + antigen-specific T cells for adoptive immunotherapy.…”
Section: T-cell Immunoglobulin and Mucin Domainmentioning
confidence: 99%